Prototype testing for the partial removal and re-penetration of the mooring dolphin platform with multi-bucket foundations. (May 2018) - Le, Conghuan; Ding, Hongyan; Zhang, Puyang
Abstract: The partial removal, adjusting, and re-penetrating tests were carried out on a mooring dolphin platform with three-bucket foundations after a seven-year service. When the bucket foundations were penetrated by internal and external pressure differential, the soil shear strength around the bucket skirt was different from that of the intact soil after installation. The side shear strength along the skirt may be increased with time due to the set-up effect. The shear strength factor α is an important time-varying factor to determine the skin friction of the foundation during installation and removal operations. The shear strength factors obtained by prototype records and theoretical methods in cohesive soils are compared, from total stress to effective stress methods. In addition, the prototype tests show that the foundations will be able to resist removal forces that are significantly larger than penetration forces due to the set-up effect after a long working time. The results show an 85% increase in the soil resistance after seven years for the three-bucket foundations with diameters of 6 m and penetration depths of 8.5 m. Meanwhile, the construction procedure and operation of the three-bucket foundations and the analysis of the extraction forces are also given for the partial removal. The test results support the successful removal by a reasonable overpressure without soil plug failure inside the buckets by controlling the pump discharge inside the buckets and reutilizing the structure with multi-bucket foundations after an initial service period of seven years. Highlights: The removal testing of MDP2 supported on a Multi-bucket foundation were performed after an initial service period of seven years. The removal tests support the successful removal by a reasonable overpressure without the soil plug failure inside the bucket. The reutilization of MDP2 with multi-bucket foundation after the re-penetration installation.